2008
DOI: 10.1177/0009922808320601
|View full text |Cite
|
Sign up to set email alerts
|

Breast-Feeding Rates at an Inner-City Pediatric Practice

Abstract: These inner-city breast-feeding rates are substantially below reported regional and national rates. Barriers to implementing urgently needed interventions are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Though the Baby-Friendly Hospital Initiative has been associated with higher rates of exclusive breastfeeding at hospital discharge in one study, 8 another concluded that the Baby-Friendly Hospital Initiative was less effective at increasing exclusive breastfeeding rates for low-income American women compared with higher income American women. 21 Our exclusive breastfeeding rate on PPD2 (31.5%) was within the range of published rates of exclusive breastfeeding at hospital discharge among low-income American women who did not deliver at Baby-Friendly Hospitals (22 22 -40% 23 ), adding weight to the concern that this initiative may not increase exclusive breastfeeding rates for low-income American women.…”
Section: Commentsupporting
confidence: 59%
“…Though the Baby-Friendly Hospital Initiative has been associated with higher rates of exclusive breastfeeding at hospital discharge in one study, 8 another concluded that the Baby-Friendly Hospital Initiative was less effective at increasing exclusive breastfeeding rates for low-income American women compared with higher income American women. 21 Our exclusive breastfeeding rate on PPD2 (31.5%) was within the range of published rates of exclusive breastfeeding at hospital discharge among low-income American women who did not deliver at Baby-Friendly Hospitals (22 22 -40% 23 ), adding weight to the concern that this initiative may not increase exclusive breastfeeding rates for low-income American women.…”
Section: Commentsupporting
confidence: 59%
“…[5][6][7] Locally, in an inner-city predominantly WICeligible population, we reported that more than 60% of mothers planned to breastfeed, yet less than 20% were still breastfeeding at all by 2 months following birth. 8,9 These data reflect an important health disparity and suggest that high-risk women are encountering obstacles in achieving their infant feeding goals.…”
Section: Introductionmentioning
confidence: 89%
“…5 Women who are both low income and urban have even lower breastfeeding rates than those who are solely low income or urban. 6 Thus, interventions are urgently needed to increase breastfeeding rates, particularly among low-income, urban, or African-American women.…”
Section: Introductionmentioning
confidence: 99%